Foliar boron spray for improved yield, oil quality and water use efficiency in water stressed sunflower - Shehzad, Muhammad Asif; Maqsood, Muhammad; Abbas, Tasawer; Ahmad, Naveed (Penerbit Universiti Kebangsaan Malaysia, 2016)
Boron (B) is a mineral considered essential for improving sunflower (Helianthus annuus L.) resistance to drought. B supplements (0, 15-, 30- and 45 mg L-1) under well-watered and variable water deficit levels (64 and 53 mm irrigation depths) were evaluated for their effects on growth, oil quality and water use efficiency (WUE) in a field study for two consecutive years (i.e. 2011 and 2012). The duration of 50% inflorescence emergence, 50% flowering and 50% maturity stages were reduced with increasing moisture stress. All B application rates improved sunflower growth compared to no B control treatment. The moisture deficit treatments of 64 and 53 mm irrigation depths significantly (p<0.05) reduced the yield-related components. Achenes/head, achenes weight and achene yield under water stress conditions were considerably improved by foliar application of B at 30 mg L-1. An increase in protein contents and a decrease in oil contents were observed with B foliar application under moisture deficit treatments. Foliar application of B (30 mg L-1) on water stressed plants also resulted in increased WUE. The highest net benefits were achieved with B concentration of 30 mg L-1 under well-watered and mild deficit water level of 64 mm irrigation depth. The highest application rate of B (45 mg L-1) gave the best results at the most severe water deficit level. In conclusion, the B rates of 30 and 41 mg L-1 performed best for improving drought tolerance in terms of higher sunflower productivity under mild and higher water deficit conditions.